2010
DOI: 10.1007/s10886-010-9790-6
|View full text |Cite
|
Sign up to set email alerts
|

High Molecular Size Humic Substances Enhance Phenylpropanoid Metabolism in Maize (Zea mays L.)

Abstract: A high molecular weight humic fraction (>3,500 Da) was characterized chemically by DRIFT and 1H NMR spectroscopy, and was applied to Zea mays L. plants to evaluate its effect on phenylpropanoid metabolism. The activity and gene expression of phenylalanine (tyrosine) ammonia-lyase (PAL/TAL), and the concentrations of phenolics and their amino acid precursors phenylalanine and tyrosine were assayed. Maximum induction of PAL/TAL activity and expression was obtained when the concentration of added humic substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 34 publications
8
121
2
5
Order By: Relevance
“…Humic substances are end products of microbial decomposition and chemical degradation of dead biota in soils (Asli and Neumann 2010, Schiavon et al 2010) and are considered to be the most abundant naturally occurring organic molecules on earth (Simpson et al 2002) and the major components of soil organic matter (Nardi et al 2002). Interestingly, dissolved humic substances are common in freshwater bodies where they have been shown to interact with freshwater organisms, a topic reviewed by (Steinberg et al 2008).…”
Section: Humic Acidsmentioning
confidence: 99%
“…Humic substances are end products of microbial decomposition and chemical degradation of dead biota in soils (Asli and Neumann 2010, Schiavon et al 2010) and are considered to be the most abundant naturally occurring organic molecules on earth (Simpson et al 2002) and the major components of soil organic matter (Nardi et al 2002). Interestingly, dissolved humic substances are common in freshwater bodies where they have been shown to interact with freshwater organisms, a topic reviewed by (Steinberg et al 2008).…”
Section: Humic Acidsmentioning
confidence: 99%
“…Schiavon et al [50] showed for the first time a relevant effect of HS on secondary plant metabolism. Plants produce a remarkably diverse array of over 100,000 low-molecular-mass natural products, also known as secondary metabolites that are distinct from the components of primary metabolism since they are generally nonessential for the basic metabolic processes.…”
Section: Changes On Primary and Secondary Metabolismmentioning
confidence: 99%
“…According to Dixon [51], most of the secondary metabolites are derived from the isoprenoid, phenylpropanoid, alkaloid or fatty/ polyketide pathways and are produced to improve plant defence against biotic and abiotic stress. Schiavon et al [50] showed that HS treatment enhanced the expression of the phenylalanine (tyrosine) ammonia-lyase (PAL/TAL; EC 4.3.1.5) that catalyzes the first committed step in the biosynthesis of phenolics, by converting phenylalanine to trans-cinnamic acid and tyrosine to p-coumaric acid. The expression of PAL/TAL was accompanied by leaf phenol accumulation.…”
Section: Changes On Primary and Secondary Metabolismmentioning
confidence: 99%
“…Although some researchers consider that HS exert multiple direct effects on plant growth in addition to "hormone-like activity", especially under abiotic stress [7,28,36], others regard the effects of humates (in the absence of plant hormones) on plant growth as being indirect: they can alter soil properties by increasing friability, buffering pH, increasing water retention, complexing trace metals and increasing their availability [37] along with that of macronutrients. For example, Fe-humate is an effective Fe source for citrus trees planted in alkaline soils, which increased tree growth and fruit production of orange and grapefruit [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Helal et al [56] showed that simple, inexpensive methods such as elemental analysis and potentiometric titration provided good agreement with the more powerful and expensive NMR and IR. Studies that include in-depth humate/humic acid characterisation include Ertani et al [26], Mora et al [28] and Schiavon et al [36].…”
Section: Future Researchmentioning
confidence: 99%